The Earthcomm Learning Model on Spatial Thinking Ability: Efforts to Strengthen the Character of Environmental Care - Memmase, Joice Zhenrike; Sumarmi; Purwanto (LPPM Undiksha, 2025)
This research is motivated by the importance of spatial thinking skills and environmental care characteristics in geography learning. This study aims to test the effect of the Earthcomm learning model on spatial thinking skills and environmental care characters of grade X students at. The type of research used is a quasi-experimental study with a pretest-posttest design. The subjects of the study involved 72 students who were divided into experimental and control groups. Data were collected through three instruments: a spatial thinking essay test (10 questions), an environmental care character strengthening questionnaire (30 questions), and Student Worksheets (LKPD) compiled based on the Earthcomm model syntax. Data were analyzed using normality and homogeneity prerequisite tests, hypothesis tests with simple linear regression, simple correlation tests, and N Gain Score tests. The results showed that the Earthcomm learning model had a significant effect on spatial thinking skills and environmental care characteristics. Simple correlation analysis showed a significant relationship between spatial thinking skills and environmental care characters. However, the N Gain Score test in the experimental group showed an effectiveness of 47.9%, which is included in the less effective category. The limited time for implementing the model in the independent curriculum is one of the factors that influence these results. This study concludes that the Earthcomm model has the potential to improve spatial thinking skills and environmental care characteristics, although its implementation requires further adjustment. These findings provide implications for the development of more effective learning models in supporting both aspects, especially in the context of a dynamic curriculum.